Antitumor Activity of Polysaccharides from Ganoderma lucidum Mycelium: in vivo Comparative Study - L. M. Krasnopolskaya; M. S. Yarina; A. V. Avtonomova; A. I. Usov; E. B. Isakova; V. M. Bukchman (Антибиотики и Химиотерапия, 2020)
Fractions of water soluble and alkali soluble polysaccharides, as well as fucogalactan, a water soluble polysaccharide, and xylomannan, an alkali soluble polysaccharide, were isolated from the Ganoderma lucidum submerged mycelium. When administered orally, the polysaccharides showed antitumor activity in vivo on murine models of solid tumors. Xylomannan and fucogalactan showed the highest antitumor activity. Sensitivity to xylomannan was more pronounced in adenocarcinoma Ca755 as compared to the T-cell lymphocytic leukemia P388. The antitumor activity of the water soluble polysaccharides total fractions from the mycelium and fruiting bodies of the G.lucidum strain was almost identical. The maximum antitumor effect of the mycelium water soluble polysaccharides total fraction was observed with the use of the daily dose of 2 mg/kg.